EVALUASI VALIDITAS ISI DAN KONSTRUK LEMBAR KERJA PESERTA DIDIK (LKPD) LARUTAN ELEKTROLIT DAN NON ELEKTROLIT BERBASIS INKUIRI TERBIMBING - ,, Humaira (Journal of Technique Research (JTR), 2019)
This research aims to produce a guided inquiry based student worksheet (LKPD) on electrolyte and non electrolyte solutions, also to determine its validity of contents and constructs of the LKPD. This research used educational design research (EDR) type, which is a research that will develop and produce a certain product. The instrument used is a validation sheet. The data from the validation sheet were analyzed by cohen cappa formula. the average kappa moment of the five validators in the content validity was 0.82 with a very high level of validity and the average kappa moment of the five validators in the content validity was 0.88 with a very high validity level. The data obtained show that the guided inquiry based student worksheet on electrolyte and non electrolyte solutions are valid of component contents and construct components.